Liver Transplantation from Voluntary Organ Donor System in China: A Comparison between DBD and DCD Liver Transplants - Wei Chen; Dipesh Kumar Yadav; Xueli Bai; Jianying Lou; Risheng Que; Shunliang Gao; Guogang Li; Tao Ma; Ji Wang; Bingfeng Huang; Tingbo Liang (Gastroenterology Research and Practice)
Background. In China, the cases of liver transplantation (LT) from donation after citizens’ death have rose year by year since the citizen-based voluntary organ donor system was initiated in 2010. The objective of our research was to investigate the early postoperative and late long-term outcomes of LT from donation after brain death (DBD) and donation after circulatory death (DCD) according to the current organ donation system in China. Methods. Sixty-two consecutive cases of LT from donation after citizens’ death performed in our hospital between February 2012 and June 2017 were examined retrospectively for short- and long-term outcomes. These included 35 DCD LT and 27 DBD LT. Result. Subsequent median follow-up time of 19 months and 1- and 3-year graft survival rates were comparative between the DBD group and the DCD group (81.5% and 66.7% versus 67.1% and 59.7%; P=0.550), as were patient survival rates (85.2% and 68.7% versus 72.2% and 63.9%; P=0.358). The duration of ICU stay of recipients was significantly shorter in the DBD group, in comparison with that of the DCD group (1 versus 3 days, P=0.001). Severe complication incidence (≥grade III) after transplantation was identical among the DBD and DCD groups (48.1% versus 60%, P=0.352). There was no significant difference in postoperative mortality between the DBD and DCD groups (3 of 27 cases versus 5 of 35 cases). Twenty-one grafts (33.8%) were lost and 18 recipients (29.0%) were dead till the time of follow-up. Malignancy recurrence was the most prevalent reason for patient death (38.8%). There was no significant difference in incidence of biliary stenosis between the DBD and DCD groups (5 of 27 cases versus 6 of 35 cases, P=0.846). Conclusion. Although the sample size was small to some extent, this single-center study first reported that LT from DCD donors showed similar short- and long-term outcomes with DBD donors and justified the widespread implementation of voluntary citizen-based deceased organ donation in China. However, the results should be verified with a multicenter larger study.